Hate Speech and Its Threat to Law Enforcement - Mathias, Jerico (The Indonesian Journal of International Clinical Legal Education, 2021)
Hate speech accompanies intellectual freedom in new media (New Media). In the context of Indonesia, this phenomenon is very important during a political event such as legislative elections (pileg), presidential election (presidential election), or elections of regional head (pilkada). Since the 2014 presidential election, the term 'haters' was widely known, titled people with golden messages hateful to certain people or groups. Especially for netizens (youth users) - the Y and Z generation, the practice of communication with these hate messages should receive special attention. In addition to the heir of the nation, this is what coloring cyberspace now. They are native to the digital world (digital native). They are aware of the right to speak and express, but understand that the online realm is the public domain inherent in normative responsibility. This paper reviews efforts to send hate messages through hate speech legislation (Hate Speech) laws and how ITE laws against hate speech acts.